Application of atosiban in frozen-thawed cycle patients with different times of embryo transfers. (2nd October 2016) - He, Ye; Wu, Huan; He, Xiaojin; Xing, Qiong; Zhou, Ping; Cao, Yunxia; Wei, Zhaolian
Abstract: This prospective cohort study aimed to examine the effects of atosiban, given before transfer of frozen-thawed embryo to women with different number of embryo transfer (ET) cycles. Atosiban treatment significantly increased implantation rate and clinical pregnancy rate in the third and more than three ET groups. However, there were no significant increases in the above parameters in the first and second ET groups. Our study showed that patients those who underwent the third or more than three ET cycles were inclined to higher uterine contractions and serum oxytocin level, thus atosiban treatment starting from the third ET cycle may be effective in improving embryo implantation. This is the first study to evaluate the optimal atosiban treatment window corresponding to the number of ET cycles of the patients.